1965
DOI: 10.1002/cber.19650981118
|View full text |Cite
|
Sign up to set email alerts
|

Umsetzung von β‐Chlor‐acroleinen mit Aminen

Abstract: Die Umsetzung von β‐Chlor‐3.4‐dimethoxy‐zimtaldehyd ergab mit Piperidin ein mesomeres, stabiles Imoniumchlorid, dessen weitere Reaktionen beschrieben werden. Der homologe β‐Chlor‐3.4‐dimethoxy‐α‐methyl‐zimtaldehyd gibt unter vergleichbaren Bedingungen das Aminal, unter energischen Bedingungen den β‐Piperidino‐aldehyd.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

1965
1965
2006
2006

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 1 publication
0
7
0
Order By: Relevance
“…The change of solvent did not affect the EE / ZE ratio; however, we observed a thermal isomerization of the stereoisomeric mixture in solution, and the percentage of the thermodynamically favored EE isomer increased 28b…”
Section: Synthesis Of Substituted 3-phenoxy-3-perfluoroalkylprop-2-enalmentioning
confidence: 58%
See 4 more Smart Citations
“…The change of solvent did not affect the EE / ZE ratio; however, we observed a thermal isomerization of the stereoisomeric mixture in solution, and the percentage of the thermodynamically favored EE isomer increased 28b…”
Section: Synthesis Of Substituted 3-phenoxy-3-perfluoroalkylprop-2-enalmentioning
confidence: 58%
“…For example, we found that enal 3c reacts easily with aniline and forms imine derivative 4 with good yields (94%) (Scheme ). Previously, the reaction of aniline with alkoxy vinyl ketones was studied, precluding a mechanism that involves a Michael addition of aniline with subsequent elimination of the alkoxy group and led to the corresponding enamino enone. 28b, In such enol ethers, the nucleophilic replacement of the alkoxy group is the predominant reaction. , In our case, only 1,2-addition product was observed probably because of steric hindrance of the perfluoroalkyl group and the high conjugation of compound 4 . To our knowledge, imino enol ether compounds have not been described yet in the literature.…”
Section: Synthesis Of Substituted 3-phenoxy-3-perfluoroalkylprop-2-enalmentioning
confidence: 61%
See 3 more Smart Citations